LEGAL PROTECTION OF COMPENSATION FOR VICTIMS OF INVESTMEN CRIME IN THE PERSPECTIVE OF ISLAMIC LAW - Santoso, Bambang; Arifin, Muhammad; Ramlan, Ramlan (Proceeding International Seminar of Islamic Studies, 2023)
Illegal investment crimes take many victims and cause huge losses for the victims, which have implications for disrupting the country's economic stability. The perpetrators are not only from within the country but across countries by using digital facilities. Islamic law strictly prohibits fraudulent acts in business and trade transactions, Islam threatens the perpetrators with severe punishment in this world and in the hereafter according to the word of Allah SWT in Surah Al-Muthoffifin verse 1 which means;